The Relationship Between Self-Management And Problem-Focused Coping With Academic Stress Among Graduate Students In Professional Psychology Programs In Surabaya - Azhar, Ryan Ainul; Suroso; Niken Titi Pratitis (Journal of Scientific Research, Education, and Technology (JSRET), 2025)
Higher education aims to help students develop their potential, but graduate students often face challenges such as thesis completion, academic demands, social pressures, and internal obstacles, triggering academic stress. This study examined the relationship between self-management and problem-focused coping with academic stress among 92 professional psychology master's students in Surabaya, using a correlational quantitative method. Data were collected via Likert-scale instruments: the academic stress scale, self-management scale, and problem-focused coping scale. Results revealed a significant negative relationship between self-management and academic stress, indicating that lower self-management abilities correlate with higher academic stress. Similarly, a significant negative relationship was found between problem-focused coping and academic stress, showing that lower coping skills are associated with greater academic pressure. These findings suggest that self-management and problem-focused coping both play crucial roles in managing academic stress among graduate students.